Impact of body mass index and waist-to-hip ratio on mortality in middle-aged Koreans: a prospective cohort study based on a Health Examinees study - Sooyoung Cho; Aesun Shin; Ji-Yeob Choi; Jong-Koo Lee; Daehee Kang (Epidemiology and Health)
OBJECTIVES We aimed to assess the impact of obesity on mortality in middle-aged Koreans using data from a Health Examinees study. METHODS We used data from the participants who had complete information on body size and gave informed consent for the linkage of their data with the national death certificate data. Cox proportional hazard model was used to estimate the hazard ratios and 95% confidence intervals (CIs) of body mass index (BMI) and waist-to-hip ratio (WHR) for all-cause, cardiovascular, and cancer mortality. RESULTS A total of 115,961 participants were included in the study. The results showed a U-shaped association between BMI and mortality, indicating that both males and females with BMIs of less than 21.0 kg/m2 and greater than or equal to 30.0 kg/m2 are at increased risk. The results showed that males with a BMI of less than 18.5 kg/m² had a significantly higher risk of all-cause mortality (adjusted hazard ratio [aHR], 2.24; 95% CI, 1.73 to 2.91) and cardiovascular mortality (aHR, 2.27; 95% CI, 1.23 to 4.20). Similarly, males with a WHR of less than 0.80 (aHR, 1.38; 95% CI, 1.08 to 1.77), 0.90 to less than 0.95 (aHR, 1.15; 95% CI, 1.02 to 1.29), and greater than or equal to 0.95 (aHR, 1.28; 95% CI, 1.11 to 1.47) showed an increased risk of all-cause mortality. In females, a BMI of less than 18.0 kg/m2 was linked to a higher risk of cardiovascular mortality (aHR, 2.67; 95% CI, 1.13 to 6.33). CONCLUSIONS Being underweight was associated with an increased risk of mortality in both sexes, and the lowest risk of death was found in males who were slightly overweight with a BMI of 23.0-25.0 kg/m2.